2020
DOI: 10.1001/jamanetworkopen.2019.21202
|View full text |Cite
|
Sign up to set email alerts
|

Resource Utilization for Patients With Distal Radius Fractures in a Pediatric Emergency Department

Abstract: IMPORTANCE Improvement of clinician understanding of acceptable deformity in pediatric distal radius fractures is needed. OBJECTIVE To assess how often children younger than 10 years undergo a potentially unnecessary closed reduction using procedural sedation in the emergency department for distal radial metaphyseal fracture and the associated cost implications for these reduction procedures. DESIGN, SETTING, AND PARTICIPANTS This retrospective cross-sectional study included 258 consecutive children younger th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 41 publications
1
13
0
2
Order By: Relevance
“…11 The authors found that 172 (56%) of the 305 children were boys and remaining 133 (44%) were girls. Similar male preponderance in the incidence of distal radius fracture was also reported by the authors such as Orland KJ et al, 12 and Syurahbil AH et al 13 In our study the mean age of affected cases in Boys and Girls was found to be 13.09 +/-2.93 years and 12.5+/-3.64 years respectively. Sengab A et al, performed a meta-analysis of 3 randomized controlled trials and 3 cohort studies, analyzing 197 patients treated with cast immobilization alone and 185 with additional K-wire fixation.…”
Section: Discussionsupporting
confidence: 90%
“…11 The authors found that 172 (56%) of the 305 children were boys and remaining 133 (44%) were girls. Similar male preponderance in the incidence of distal radius fracture was also reported by the authors such as Orland KJ et al, 12 and Syurahbil AH et al 13 In our study the mean age of affected cases in Boys and Girls was found to be 13.09 +/-2.93 years and 12.5+/-3.64 years respectively. Sengab A et al, performed a meta-analysis of 3 randomized controlled trials and 3 cohort studies, analyzing 197 patients treated with cast immobilization alone and 185 with additional K-wire fixation.…”
Section: Discussionsupporting
confidence: 90%
“…13,14 The cost of reduction is also far greater, ranging from 50% to 700% more than non-reduction treatment. 5,15 Figure 1 shows the radiographs of a 6-year-old male who sustained a distal radius and ulna fracture after a fall at a playground. Radiographs at one-week post-injury were significant for 30° of apex volar angulation and 25° of radial angulation (Figure 1a).…”
Section: Key Conceptsmentioning
confidence: 99%
“…Patients undergoing ED reduction spend two hours longer in the ED than those undergoing nonreduction treatment. 5,15 Crawford et al found that ED reduction and casting cost $3,819 more than an office visit application of a cast ($4,846 vs. $1,027). 4 Orland et al performed a cross-sectional study at a single tertiary pediatric emergency room in the USA and found that the cost difference between those reduced and not reduced was estimated at approximately $7,000 ($8,077 vs. $1,027).…”
Section: Costmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13] It has been suggested that it is unnecessary to perform reduction maneuvers in pediatric patients with distal radius factures because of their marked remodeling potential, 2,3,7,[14][15][16][17][18][19] and furthermore, performance of closed reduction results in increased cost, patient risk, hospital time, and provider time. 14,20,21 In addition, closed reduction of pediatric distal radius fractures commonly requires sedation to minimize patient pain and to allow for more anatomic reduction, which subjects patients to risks of sedation including respiratory depression, hypoxia, hypotension, nausea, and aspiration. [21][22][23][24] The purpose of this study was to determine what percentage of 100% displaced pediatric distal radius fractures that undergo closed reduction develop unacceptable angulation, rates of failure requiring repeat intervention including second sedation procedures, cast changes, and extra clinic visits, and the added expense, if any, associated with sedated emergency department (ED) reduction.…”
mentioning
confidence: 99%